Structural Insights Into Tautomeric Dynamics in Nucleic Acids and in Antiviral Nucleoside Analogs - Fedeles, Bogdan I.; Li, Deyu; Singh, Vipender (Frontiers in Molecular Biosciences, 2022)
DNA (2’-deoxyribonucleic acid) and RNA (ribonucleic acid) play diverse functional roles in biology and disease. Despite being comprised primarily of only four cognate nucleobases, nucleic acids can adopt complex three-dimensional structures, and RNA in particular, can catalyze biochemical reactions to regulate a wide variety of biological processes. Such chemical versatility is due in part to the phenomenon of nucleobase tautomerism, whereby the bases can adopt multiple, yet distinct isomeric forms, known as tautomers. For nucleobases, tautomers refer to structural isomers that differ from one another by the position of protons. By altering the position of protons on nucleobases, many of which play critical roles for hydrogen bonding and base pairing interactions, tautomerism has profound effects on the biochemical processes involving nucleic acids. For example, the transient formation of minor tautomers during replication could generate spontaneous mutations. These mutations could arise from the stabilization of mismatches, in the active site of polymerases, in conformations involving minor tautomers that are indistinguishable from canonical base pairs. In this review, we discuss the evidence for tautomerism in DNA, and its consequences to the fidelity of DNA replication. Also reviewed are RNA systems, such as the riboswitches and self-cleaving ribozymes, in which tautomerism plays a functional role in ligand recognition and catalysis, respectively. We also discuss tautomeric nucleoside analogs that are efficacious as antiviral drug candidates such as molnupiravir for coronaviruses and KP1212 for HIV. The antiviral efficacy of these analogs is due, in part, to their ability to exist in multiple tautomeric forms and induce mutations in the replicating viral genomes. From a technical standpoint, minor tautomers of nucleobases are challenging to identify directly because they are rare and interconvert on a fast, millisecond to nanosecond, time scale. Nevertheless, many approaches including biochemical, structural, computational and spectroscopic methods have been developed to study tautomeric dynamics in RNA and DNA systems, and in antiviral nucleoside analogs. An overview of these methods and their applications is included here.